Brochure on Preparation and Maintenance of Confidential Reports - Department of Personnel and Training, Ministry of Personnel, Public Grievances and Pensions, Government of India (Department of Personnel and Training, Ministry of Personnel, Public Grievances and Pensions, Government of India, 1987)
The performance of Government is ultimately the sum total of the performances of the individuals through which it functions. Government has, therefore, to know from time to time how its constituents function. This information is essential for proper Personnel Administration and Management. It is in the interest of every Government servant that he should know how well or otherwise, he is performing his job. Without this feed back information, it will be difficult for him to plan his career development in a systematic manner. In fact, he would be more interested in knowing his defects. His defects would affect his career advancements in the long run. unless he comes to know of them in time and overcomes them by taking special efforts.
Government of India, Department of Personnel and Training, Ministry of Personnel, Public Grievances and Pensions
Government of India, Department of Personnel and Training, Ministry of Personnel, Public Grievances and Pensions